The abbot's tale : a novel - Iggulden, Conn (Pegasus Books, 2018)
In the year 937, the new king of England, a grandson of Alfred the Great, readies himself to go to war in the north. His dream of a united kingdom of all England will stand or fall on one field--on the passage of a single day. At his side is the priest Dunstan of Glastonbury, full of ambition and wit (perhaps enough to damn his soul). His talents will take him from the villages of Wessex to the royal court, to the hills of Rome--from exile to exaltation. Through Dunstan's vision, by his guiding hand, England will either come together as one great country or fall back into anarchy and misrule...From one of our finest historical writers, The Abbott's Tale is an intimate portrait of a priest and performer, a visionary, a traitor and confessor to kings--the man who can change the fate of England.--Dust jacket.